1988
DOI: 10.1136/oem.45.6.376
|View full text |Cite
|
Sign up to set email alerts
|

Allergy and occupational exposure to hydroquinone and to methionine.

Abstract: Respiratory manifestations have been reported after exposure to hydroquinone and to methionine. One hundred and three men in the same chemical plant were divided into three groups according to their exposure and compared by questionnaire, respiratory functional tests with methacholine then salbutamol challenges, and measurements of serum immunoglobulins G and E. Group H included 33 workers exposed to hydroquinone, trimethyl-hydroquinone, and retinene-hydroquinone. Group M included 15 workers exposed to methion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Choudat and co-workers 338 reported an increase in respiratory symptoms (i.e., cough in a smoky atmosphere and hay fever) in workers exposed by inhalation to a combination of HQ, trimethyl-HQ, and retinene-HQ (relative and absolute concentrations of each compound not specified). Decreased pulmonary function test results (i.e., decreased forced expiratory volume and vital capacity) and elevated serum IgG were reported.…”
Section: A Systemic Effectsmentioning
confidence: 96%
“…Choudat and co-workers 338 reported an increase in respiratory symptoms (i.e., cough in a smoky atmosphere and hay fever) in workers exposed by inhalation to a combination of HQ, trimethyl-HQ, and retinene-HQ (relative and absolute concentrations of each compound not specified). Decreased pulmonary function test results (i.e., decreased forced expiratory volume and vital capacity) and elevated serum IgG were reported.…”
Section: A Systemic Effectsmentioning
confidence: 96%
“…A study on occupational exposure of hydroquinone showed that subjects exposed to hydroquinone had a higher prevalence of cough and decreased lung capacity compared to their unexposed counterparts 41 .…”
Section: Formaldehydementioning
confidence: 99%